Effect of Soil Working on Ravine Afforestation - Pradhan, I. P.; Dayal, Rajbans (Indian Forester, 1973)
Various types of continuous, staggered contour trenches and pits were tried at Soil Conservation Research Farm. Vasad, for afforestation with Acacia arabica (Willd). Staggered contour trench of 3 m × 45 cm × 60 cm depth with raised mound of 1 m × 60 cm height (T4) was found to be the most suitable one giving mean height of 452.67 cm and diameter (collar), of 7.52 cm at the end of fourth year. It was followed by staggered contour trench of 3 m × 30 cm × 45 cm depth with raised mound of 1 m × 45 cm height (T3) and continuous contour trench of 30 cm × 45 cm depth with raised mound of 1 m × 30 cm height (T2)